Reverse Logistics Implementations Solutions: Interval Type 2 FAHP-FTOPSIS Approach - Sedigheh Solati; Payam Shojaei; Moslem Alimohammadlou; Zahra Heidari Hesamabadi (Discrete Dynamics in Nature and Society)
In recent years, reverse logistics (RL) has come to the fore as an important issue, given the increasing environmental concerns, corporate social responsibility, and sustainable competition. Today, RL is considered a strategic activity. Legal requirements, social responsibilities, environmental concerns, economic interests, and customer awareness have led manufacturers to produce eco-friendly products and to collect returned and used products. Nevertheless, there are barriers to the implementation of RL in organizations. This study sought to prioritize solutions for overcoming the barriers to the implementation of RL in the Iranian iron and steel industry. To analyze the data, interval type-2 fuzzy AHP (FAHP) and fuzzy TOPSIS (FTOPSIS) have been used. The results revealed that “policy-related issues,” “knowledge-related issues,” and “economic issues” were the key barriers and showed the highest ranks, respectively. Furthermore, the results indicated that “strategic collaboration with reverse chain partners,” “using advanced technologies for waste collection,” and “transparent quality and product value” were the major measures to overcome the barriers. The proposed model suggests that decision-makers should consider long-term relations with supply chain partners in organizations to implement RL.